2012
DOI: 10.1021/jo301203k
|View full text |Cite
|
Sign up to set email alerts
|

High-Pressure-Promoted Diels–Alder Approach to Biaryls: Application to the Synthesis of the Cannabinols Family

Abstract: Diels-Alder reactions of a range of 1-(alkoxy/alkyl/halogen-substituted phenyl)buta-1,3-dienes with methyl propiolate carried out in a green ethanolic medium under 9 kbar pressure were investigated. The use of high pressure as activating method of the Diels-Alder reactions allows efficient and regioselective generation of a series of cyclohexadienyl-benzene cycloadducts that are oxidized to the corresponding biaryls. The alkoxy/alkyl/halogen-substituted biaryls produced are useful precursors for accessing subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 78 publications
0
13
0
Order By: Relevance
“…The resulting biaryl carboxylic acid 6 was converted into dimethyl isourolithin A 7 by treatment with NIS in dichloroethane . Deprotection of the phenolic substituents delivered the expected natural product 8 in excellent yield.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting biaryl carboxylic acid 6 was converted into dimethyl isourolithin A 7 by treatment with NIS in dichloroethane . Deprotection of the phenolic substituents delivered the expected natural product 8 in excellent yield.…”
Section: Resultsmentioning
confidence: 99%
“…Our research group has recently identified high pressure‐promoted Diels‐Alder reaction as a key step to accomplish metal‐free synthesis of biaryls, even achieving the total synthesis of biaryl‐containing biologically active natural compounds in a few steps , . Coupling this strategy with the advantages of multicomponent reactions to generate in situ an electron‐rich diene, a palette of functionalised aromatics has been prepared under hyperbaric conditions , …”
Section: Introductionmentioning
confidence: 99%
“…The advantages of the above-described high pressure activation approach to biaryls 47 have been demonstrated by the efficient and environmentally friendly generation of a broad series of substituted 6 H -benzo[ c ]chromen-6-ones ( 48 type), including the total synthesis of natural cannabinol (Scheme 14). 58…”
Section: Tandem Cycloaddition and Related Processes Under Hyperbaric ...mentioning
confidence: 99%
“…Functionalized biaryl scaffolds 46 were obtained in almost quantitative yields during the highpressure-promoted [4 + 2] cycloaddition between methyl propiolate and butadienes 45 (Scheme 14). [55][56][57][58] The easily isolated cyclohexadiene intermediates 46 can be further subjected to a bromination/dehydrobromination procedure or dehydrogenation with DDQ (2,3-dichloro-5,6-dicyanobenzoquinone) to give the corresponding biphenyls 47 after aromatization. The data reported in one paper 58 emphasize once again the benefits of high pressure.…”
Section: Organic and Biomolecular Chemistry Reviewmentioning
confidence: 99%
“…Besides oxidative aromatization of tetrahydrocannabinols,7a,b,10 other strategies for the synthesis of cannabinols include formation of the biaryl moiety by nucleophilic aromatic substitution or cross‐coupling reactions followed by pyran formation,9,11 and construction of the second phenyl ring starting from a suitably substituted arene by various cyclization reactions including an Ru‐catalyzed microwave‐mediated [2+2+2] cyclotrimerization reaction12 and a multicomponent domino reaction 13. Recently, Minuti and co‐workers have developed a high pressure‐promoted Diels–Alder reaction of 1‐phenylbuta‐1,3‐dienes with methyl propiolate for the synthesis of phenylcyclohexadienes, which was also applied to the formal synthesis of cannabinol ( 2 ) 14. However, the very high pressure (9×10 3 bar) required to secure a good yield of the products and the necessity for a separate oxidation step to produce the biaryls is rather inconvenient.…”
Section: Introductionmentioning
confidence: 99%